An Examination of the Role of Values in Counselling and Psychotherapy - Dragan, Jerry (Canadian Journal of Counselling and Psychotherapy, 2012)
Counsellors and therapists alike have struggled for some time to ascertain whether or not there is a legitimate role for values in counselling and psychotherapy. From early attempts to keep the counselling process value-free, practitioners have moved to the point where they now question whether they can, with integrity, "remain objective." This paper contends that the question begs the point, i.e., that values significantly influence the counsellor's choice of a psychotherapeutic theory, selection of clients, counselling techniques, treatment goals, and direction of improvement. In fact, the entire therapeutic process is monitored in treatment by a formalized value-system — the therapist's code of ethics. The question then is not whether values belong in therapy, but whether it is possible to train counsellors and therapists to the level where their own values do not interfere with the goals, methods, and directions required by the client for problem-solving.